Antecedents Of Memorable Rural Tourism Evidence From Indonesian Traveler - Juliana Juliana; Ferdi Antonio (LPPM Universitas BSI, 2022)
ABSTRACTThe purpose of this study was to examine the arousal and memorable rural experience that had an effect on revisitation intention, willingness to pay rural product, positive e-wom. The population of this study is tourism visiting tourist villages in Indonesia. The sample in this study were 200 respondents. This research is a quantitative research with survey method. Data collection tools in this study using a questionnaire. Online questionnaires distributed to domestic tourists who visit tourist villages to respondents using the Non Probability Sampling approach using purposive sampling with the criteria that tourists have visited once a year a tourist village in Indonesia. Data analysis using PLS-SEM. The results of the study there is one variable that is not significant, namely the ACBT variable on Arousal. Meanwhile, Education, Entertainment, Escapism, Esthetics have a significant and positive effect on arousal and the Memorable Rural Tourism experience variable has a significant and positive effect on Revisiting Intention, Willingness to pay rural product, Willingness to share positive e-wom. This study also offers other areas that deserve more research from the perspective of practitioners and researchers. Keyword : Arousal, Memorable Rural Tourism Experience, revisitation intention, willingness to pay rural product, positive e-wom